2016
DOI: 10.1111/1365-2656.12606
|View full text |Cite
|
Sign up to set email alerts
|

Like a rolling stone: the dynamic world of animal ecology publishing

Abstract: It has been another successful and busy year at Journal of Animal Ecology, with a number of new initiatives and an increase in Journal activity, with total submissions increasing by 13% over the last year, the number of open access papers increasing to an all-time high, and our impact factor increasing to 4Á827. We also welcomed in 12 new Associate Editors and said goodbye to eight others. We would like to thank them all for their dedicated service to the Journal, but reserve special thanks to Simon Butler, Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…In our longitudinal dataset, many individuals appeared to show an increase in TL (Fig. S2); moreover, other recent longitudinal studies of wild animals have reported similar within-individual increases in TL over time ( Fairlie et al, 2016 , Spurgin et al, 2017 ). In humans, telomerase is expressed during spermatogenesis, and continuously dividing sperm cells exhibit longer telomeres than somatic cells ( Aston et al, 2012 ).…”
Section: Discussionsupporting
confidence: 76%
“…In our longitudinal dataset, many individuals appeared to show an increase in TL (Fig. S2); moreover, other recent longitudinal studies of wild animals have reported similar within-individual increases in TL over time ( Fairlie et al, 2016 , Spurgin et al, 2017 ). In humans, telomerase is expressed during spermatogenesis, and continuously dividing sperm cells exhibit longer telomeres than somatic cells ( Aston et al, 2012 ).…”
Section: Discussionsupporting
confidence: 76%
“…While many of the editorial boards from journals in this study report advances in recruiting women and minorities into their ranks over recent years [ 16 , 19 ], we nonetheless find that women and minorities were still significantly more likely to author published papers than to edit them ( Fig 1 ). Furthermore, minority editorial board members were less-likely to serve as handling editor on publications than their majority peers ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 71%
“…Even background awareness about editor-author interactions may reduce resulting biases moving forward. The journals studied here have all made efforts in recent years to add diversity to their editorial staffs [ 19 ], and the ecological research culture continues to make great strides to mitigate biases. We hope that this analysis encourages authors to proactively consider recommending editors with gender and institutional features different from their own, especially in cases where those features have limited implications for the science at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Merogony (asexual reproduction) of Haemoproteus occurs in other tissues, whereas Plasmodium multiplies also in red blood cells leading to their disintegration (Valkiūnas 2005 ; Valkiūnas and Iezhova 2017 ). Blood pathologies induced by parasitaemia are expected to increase demand for new blood cells (Schoenle et al 2017 ), which can be attained through higher number of cellular divisions, possibly leading to pronounced telomere erosion. Due to the differences in life cycles between the haemosporidian parasites, lesser impact of Haemoproteus on blood TL is expected.…”
Section: Introductionmentioning
confidence: 99%